Overcoming mcr-1 mediated colistin resistance with colistin in combination with other antibiotics - Craig R. MacNair (Nature Portfolio, 2018)
The plasmid-borne mcr-1 gene confers resistance to the antibiotic colistin. Here, MacNair et al. show that mcr-1 positive bacteria are however susceptible to colistin-mediated disruption of the outer membrane, and can be killed in vitro and in vivo by combining colistin with other antibiotics.